Use of Learning Media to Increase Student Learning Motivation in Junior High Schools - Charline, Canti; Jo, Servais; Frederic, Ehx (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The development of the times greatly influences life, one of which is in the field of education, there are many innovations related to education, one example is the use of learning media in teaching and learning processes and motivation. Lots of learning innovations that produce technology that makes it easier for an educator to provide learning material so that students get motivation to learn. Learning media is very useful in every lesson at the junior high school level. This study aims to determine the application of the use of any media that can influence and encourage students' learning motivation at the junior high school level. This type of research is descriptive qualitative research. Data obtained through observation, interviews and documentation. The results of the study show that the use of learning media on students' learning motivation greatly supports motivation in learning activities. The students were highly motivated when the learning used projector and speaker media. In addition, the use of learning media at the junior high school level has an important role in the interest and motivation of students' learning, including feelings of pleasure and interest in the material increasing. The implication of this research is that educators in delivering learning material in class must be good at choosing and using the right media, educators must also have creative and innovative ideas so that the learning atmosphere of students is more enthusiastic and motivated. The limitation of this research is that the researcher only observed one school, therefore the researcher hopes that future researchers will be able to observe more schools and in a better way.